New olefin production routes—A review of defossilised supply chain technologies with regards to surfactant production - Platt, Edward G.; Styring, Peter (Frontiers in Sustainability, 2022)
With “defossilisation” at the core of many sustainability goals within industry, the exploration of new synthesis routes to chemicals has never been more vital. As part of their Clean Futures initiative, Unilever Home Care has published the Carbon Rainbow, a scheme which categorises chemical sources into different “colours”, depending on their derivation. One of the sustainability goals of the Carbon Rainbow is to phase out non-renewable “black” carbon from supply chains by 2030. This complements the goals of the Clean Futures initiative, which looks towards a Net-Zero impact from all products from a cradle-to-shelf scope by 2039. Given the substantial contributions to atmospheric CO2 emissions from the production and use of conventional surfactants, this paper reviews methods to form Linear Alkylbenzene Sulfonate (LAS) through means which look to utilise Carbon Rainbow-categorised carbon sources outside of traditional fossil sources. The focus when reviewing each method is the overall defossilisation of the LAS production process. The inventories of new defossilised methods collated within this research will ultimately provide the backbone for a future study on sustainability assessment screening. Through a literature search and technological overview, the construction of a tree diagram showing many new routes to LAS-appropriate olefins has been accomplished, illustrating the breadth of technologies available that share the common goal of defossilisation. The expanse of technologies works well as to provide options to the necessary companies, though also resulting in a vast array of options to consider and assess before pursuing the optimum route. In total, nineteen technologies were reviewed, forming a map containing twenty-seven different supply chain routes from feedstock to LAS-appropriate olefins. This research therefore also shows the need for a short-form sustainability screening in order to green-light technologies which are suitable for a long-form sustainability assessment before any new process is adopted.